(3TQM GdUOhQ HGdUdGI hGdSdGe Ydi GdfGUQ GdefUhQs - (3Gdedhj GdeLjQj GdTGaYqj GdCRgQj, CHh GdYHGS, TgGH GdOjf, CMeO Hf YHO GdaJGM Hf jhSa, J(B1181(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO ajbhdCMeO Hf YHO GdaJGM GdTGaYj GdeLjQj Gdedhj gPg UdhGJ Ydi GdfHjhSejJgG TQM GdUOhQ HGdUdGI hGdSdGe Ydi GdfGUQ GdefUhQs
(3BNQgG (B:s
(3Gddge Ud Ydi SjOfG eMeO GdfHj GdCej hYdi Bdg hUMHg hSde UGMH GdYWGjGs
(3fSNI efbhdI ef fSNI GdeDda GdeDQNI SfI (B1142(3g` , aj BNQg COYjI hahGFO aj GdJUhas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 152s
(3eYLe GdeDdajf(B: 1 / 172s
(3EjVGM Gdecfhf(B: 2 / 45s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs